Opinions and Expectations of Muslim Donors' Relatives Deciding Organ Donation: The Sample of Istanbul - Harmanci Seren, Arzu Kader (Journal of religion and health, 2018)
The low rate of consent by relatives of potential donors especially in Muslim majority countries is one of the basic limiting factors of the success of organ transplantation. Therefore, this study aimed to explore opinions and expectations of relatives after donating their beloved ones' organs on a Muslim sample in Istanbul Region. Descriptive method was used. Data were collected from 82 of 95 Muslim donor relatives who agreed to participate in the study between the March and July 2014 via telephone calls. It was found that most of the relatives had donated the organs of their relatives for keeping alive the beloved ones' organs in others' bodies instead to send them to the soil. Less of the relatives expressed regret for donating due to not introducing to the recipients. Muslim donor families also expect priority in hospitals and priority for transplantation if they have another relative waiting for organ transplantation.